Cisplatin resistance in mouse fibrosarcoma cells after low-dose irradiation in vitro and in vivo. - Eichholtz-Wirth, H. (Nature Publishing Group, 1994)
Murine fibrosarcoma cells (SSK) exhibit a transient cisplatin resistance after low-dose irradiation (5 x 2 Gy) in vitro and in vivo. When resistance is lost, it can be restored by a single drug exposure which, without preirradiation, does not generate cisplatin resistance in parental cells. There is no cross-resistance to radiation. Metallothioneins, which are associated with cisplatin resistance after high-dose irradiation (15 x 6 Gy), do not correlate with induction and loss of cisplatin resistance after low-dose irradiation. Since cisplatin survival curves are also monotonous when drug resistance diminishes, an adaptive response is more likely than a mutational event to underlie cisplatin-induced resistance. Drug resistance can be overcome by combined exposure to cisplatin in the presence of the phosphodiesterase inhibitor 3-isobutyl-1-methylxanthine (IBMX). Under these conditions, cisplatin sensitivity is increased 2.4- to 2.8-fold in the resistant strains compared with only 1.5- to 1.8-fold in the parental cells. The cellular platinum content with and without IBMX treatment is not significantly different in sensitive and resistant cells. Loss of drug resistance correlates with a decrease in cisplatin sensitisation by IBMX. This suggests that cisplatin resistance after low-dose irradiation may be associated with alterations of the cAMP-dependent signal transduction pathway.